The Efficacy of Pectoralis Nerve Blockade in Breast Reductions: A Prospective Randomized Trial. Issue 5 (June 2021) - Wallace, Chelsea C.; Wetzel, Margaret E.; Howell, Christopher; Vasconez, Henry C.
Abstract : Background: Pectoralis nerve (Pecs) blocks have been shown to reduce perioperative opioid consumption in patients undergoing mastectomies, but the effectiveness of these blocks in breast reductions has not been established. This trial aims to evaluate the efficacy of Pecs blocks (I and II) on perioperative pain management in patients undergoing breast reductions. Methods: Thirty-six patients were enrolled in the randomized controlled trial divided into 2 groups. The treatment group (n = 16) received general anesthesia plus postinduction ultrasound-guided Pecs blocks. The control group (n = 20) received general anesthesia alone. The primary outcomes measured were perioperative narcotic requirements, need for postoperative antiemetics, pain scores, and length of time in the operating room (OR). We measured patient and procedural risk factors including pedicle/skin excision patterns, concurrent liposuction, weight of resection, and additional local anesthesia. Risk factors as well as outcomes were analyzed using Fischer exact and t tests. Results: No statistically significant difference was shown between the group receiving the Pecs blocks and the control with regard to narcotic requirements, pain scores, and need for antiemetics. Patients undergoing Pecs blocks had a significantly higher OR time before incision ( P = 0.0073). Patient and procedural risk factors were well balanced ( P > 0.41). Conclusions: Pectoralis nerve blocks may be a valuable component of a multimodality pain regimen; however, when performed as a solitary adjunct, they do not seem to decrease perioperative narcotic requirements, pain scores, or the need for antiemetic medication in patients undergoing breast reductions. In addition, postinduction Pecs blocks significantly increase OR times.